THE ENIGMA OF BUDDHISM: DUHKHA AND NIRVANA - Mathai, B. K. (Journal of Dharma, 1977)
"The scriptures are unalterable and the comments often enough merely express the commentator's bewilderment." F. Kafka In the present note I wish to express, as a modern comment- ator, my own bewilderment about the notion of dukka or suf- fering, which is admittedly a very basic concept of the Indian religious traditions. It is well-known that the doctrine of dukkha or universal suffering is an essential part of the central teaching of the Buddha. The four noble truths taught by the Buddha are: clu~kha (suffering, pain, anguish), origin or cause of suffering, ces- sation of suffering, and the Way. The Yoga Sutras also talk of a similar model, which shows that the model was simply unique to Buddhism. Vyasa, for example, says while commenting upon Yogasutra 2: 15.